2022
DOI: 10.1155/2022/7000390
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Population Structure and Regional Innovation Ability Based on Big Data Analysis

Abstract: With the continuous advancement of the urbanization process, the scale of cities has expanded rapidly, and the amount of floating population has grown rapidly. Big data not only brings changes in thinking, technology, and management but also promotes the renewal and development of social governance concepts, technologies, methods, and models, which creates new opportunities for urban floating population governance innovation. City governments at all levels are facing enormous management pressure and urgently n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The global spatial autocorrelation analysis focuses on whether the attribute variables are aggregated from the whole study area, and its formula is as follows [7].…”
Section: Spatial Autocorrelation Analysis Methodsmentioning
confidence: 99%
“…The global spatial autocorrelation analysis focuses on whether the attribute variables are aggregated from the whole study area, and its formula is as follows [7].…”
Section: Spatial Autocorrelation Analysis Methodsmentioning
confidence: 99%
“…Population is a critical carrier of material flow, information flow, capital flow, and technology flow. The migration of populations among various cities is often regarded as the spatial reconfiguration of production factors [ 14 , 15 ]. Studies have shown that changes in the industrial structure will affect labor demand at different levels, which is a crucial factor in population migration among adjacent cities in modern society.…”
Section: Theoretical Frameworkmentioning
confidence: 99%